2019
DOI: 10.1093/jas/skz053.023
|View full text |Cite
|
Sign up to set email alerts
|

15 Future-proofing the feedyard workforce: Survey of Texas beef cattle stockpeople indicates positive attitudes towards animals and the workplace while highlighting opportunities for improvement

Abstract: A survey was administered to Texas cattle feedyard employees (n = 111) from 31 different operations measuring stockperson perception, job satisfaction and socioeconomic status using Likert statements and multiple-choice questions. Differences among employment roles (manager, pen rider, processor, doctor) were evaluated using a Kruskal-Wallis test followed by a Multiple Comparison procedure. Managers more strongly agreed that “beef cattle are not dirty” than doctors (P = 0.03) and that “cattle behavior is affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, dairy caretakers that underwent case-study based training for treatment decisions such as euthanasia stated that while they felt confident in making euthanasia decisions before the case study discussion, the training experience was still beneficial in improving their euthanasia decision-making skills (42). A 2019 survey of pen riders from 31 Texas feedlots indicated that feedlot pen riders are less confident in performing euthanasia than managers and veterinarians and were more likely to indicate that cattle are not always euthanized in a timely manner (43). Primary research focusing on clarifying ambiguity in euthanasia guidelines and increasing confidence in euthanasia decision-making by providing clear animalbased outcomes and defined endpoints are needed to ensure timely euthanasia of ill and injured feedlot cattle.…”
Section: Dispositions and Welfare Considerationsmentioning
confidence: 99%
“…For example, dairy caretakers that underwent case-study based training for treatment decisions such as euthanasia stated that while they felt confident in making euthanasia decisions before the case study discussion, the training experience was still beneficial in improving their euthanasia decision-making skills (42). A 2019 survey of pen riders from 31 Texas feedlots indicated that feedlot pen riders are less confident in performing euthanasia than managers and veterinarians and were more likely to indicate that cattle are not always euthanized in a timely manner (43). Primary research focusing on clarifying ambiguity in euthanasia guidelines and increasing confidence in euthanasia decision-making by providing clear animalbased outcomes and defined endpoints are needed to ensure timely euthanasia of ill and injured feedlot cattle.…”
Section: Dispositions and Welfare Considerationsmentioning
confidence: 99%